2016
DOI: 10.4174/astr.2016.91.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Use of fibrin glue in preventing pseudorecurrence after laparoscopic total extraperitoneal repair of large indirect inguinal hernia

Abstract: PurposeSeroma is among the most common complications of laparoscopic total extraperitoneal (TEP) for especially large indirect inguinal hernia, and may be regarded as a recurrence by some patients. A potential area localized behind the mesh and extending from the inguinal cord into the scrotum may be one of the major etiological factors of this complication. Our aim is to describe a novel technique in preventing pseudorecurrence by using fibrin sealant to close that potential dead space.MethodsForty male patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…In addition, the conditions of the hospital and the laparoscopic technique and experience of the surgeons were also important factors that must be considered. Otherwise it might produce unnecessary recurrence and complications [13,14]. This study indicated that the cost of surgery in TEP group and TAPP group was significantly higher than that in Lichtenstein group.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, the conditions of the hospital and the laparoscopic technique and experience of the surgeons were also important factors that must be considered. Otherwise it might produce unnecessary recurrence and complications [13,14]. This study indicated that the cost of surgery in TEP group and TAPP group was significantly higher than that in Lichtenstein group.…”
Section: Discussionmentioning
confidence: 65%
“…Pini et al sutured the transversalis fascia with V-Loc suture on 61 r-TAPP sites and observed neither seroma nor recurrence after 30 days, and no prolonged or chronic pain over a 10-month follow-up [25]. There is one small randomized trial of fibrin sealant in 40 patients, showing that seroma prevention is significant in the intervention group (p < 0.001; [26]). In the current series, 17 of 20 seromas were observed in lateral hernias, of which only 1 patient had been sealed with fibrin glue.…”
Section: Discussionmentioning
confidence: 99%
“…haben an 61 r‑TAPP-Seiten die Fascia transversalis mit V‑Loc-Naht gerafft und nach 30 Tagen weder ein Serom noch ein Rezidiv sowie keine prolongierten oder chronischen Schmerzen in einem Follow-up von 10 Monaten beobachtet [ 25 ]. Zur Fibrinkleberversiegelung liegt eine randomisierte Studie vor, die an 40 Patienten zeigt, dass die Seromprophylaxe signifikant ist ( p < 0,001; [ 26 ]). In der aktuellen Serie sind 17 von 20 Seromen bei lateralen Hernien beobachtet worden, von denen nur 1 Patient mit Fibrinkleber versiegelt worden war.…”
Section: Diskussionunclassified